Desain Pembelajaran Pendekatan Discovery Learning dengan Menerapkan Pembelajaran dari Finlandia - Cidi Cindiawati; Flavia Aurelia Hidajat (Griya Journal of Mathematics Education and Application, 2022)
This study aims to provide alternative solutions from learning using discovery learning approach learning design by applying learning from Finland. A learning design is used to create a learning model in this piece of literature. Students' requirements are taken into consideration throughout the development process. Discussed in depth, learning outcomes are tailored to the instructional goals. As a consequence of the findings of this research, educators who want to teach statistics using group data may consider adopting a method inspired by Finnish research and practice. This lesson is divided into small parts and starts from the basic understanding of statistics that students need.